THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE'S PERFORMANCE IN COMMISSION GENERAL ELECTION BUKITTINGGI - Hariman Syaleh (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2019)
ABSTRACT This study aims to see